Evolution of an Endovenous Laser Ablation Practice for Varicose Veins. (August 2013) - Samuel, N; Wallace, T; Carradice, D; Smith, G; Mazari, F; Chetter, I
Objective: We aimed to assess the evolution of an endovenous laser ablation (EVLA) practice in the management of varicose veins in a university teaching hospital vascular surgical unit, over five years. Methods: This was a retrospective review of a prospectively collected database of patients undergoing EVLA for great saphenous vein incompetence and followed up for a year. For inter- and intragroup comparison, patients were divided into three groups: group A: endovenous access generally established at the perigenicular level ( n = 105); group B: when practice changed to gain access at lowest point of demonstrable reflux ( n = 70); and group C: when tumescence delivery changed from manual injections to delivery via peristaltic pump ( n = 49). Outcomes including pain scores, time taken to return to normal functioning, quality of life (QoL), venous clinical severity scores (VCSS) and complication rates were evaluated. Results: Intergroup analysis: increase in the length of vein treated and laser density delivered was observed over time, even as median procedure duration decreased ( P < 0.001). An increase in sensory disturbance was noticed in group C ( P = 0.047) while better Aberdeen Varicose Vein Questionnaire (AVVQ) ( P = 0.004), SF-36 ® physical domains ( P < 0.05) and patient satisfaction with treatment ( P = 0.025) were recorded in the same group at 52 weeks. No significant difference was observed in technical failure, pain scores, return to normal functioning, VCSS and recurrence rates post-intervention. Intragroup analysis: QoL measures (AVVQ, SF-36 ®, EQ-5D) and VCSS scores demonstrated significant improvement at 12 and 52 weeks compared with baseline ( P < 0.05). Conclusions: Increase in length of vein treated and energy delivery seems to improve short-term outcomes; however, operators need to be wary of a possible concurrent increase in paraesthetic complications.